Validity of 1-compartment model for urea on adequate dialysis - NAKAZATO, S; ERA, K; OTA, K; SANAKA, T; HOSHINO, T; TERAOKA, S; AGISHI, T; MINESHIMA, M; KUBO, K (Jinko Zoki, 1993)
Adequate dialysis for each patient was established through a 1-compartment model for urea. 78 subjects with CRF who received HD treatments 3 times a week participated in this study. Blood samples were collected at pre- and post-treatment on midweek-dialysis and pre-treatment on weekend dialysis in a week. Substituting BUN values obtained from samples into the analytical solutions of 1-compartment model yielded Kt/V, G/V and estimated time-averaged concentration(TACest) for urea. Clinical TAC value(TACclin) defined as the timeaveraged BUN of samples has a good correlation with TACest as follows: TACclin=0.643 TACest+13.1 (r=0.898). TACclin values, however, indicate about 8.2% smaller than TACest values because changes of V and G were ignored in the 1-compartment model.